BODY COMPOSITION COMPONENTS IN PATIENTS WITH CHRONIC HEART FAILURE AND TYPE 2 DIABETES MELLITUS - Davronov Donyorjon Burkhonjon ugli (World Scientific Research Journal, 2025)
There is growing evidence that body composition should be considered as a systemic marker of disease severity in chronic organ diseases such as chronic obstructive pulmonary disease, chronic kidney disease, and chronic heart failure (CHF). This article focuses on changes in body composition components in patients with chronic heart failure and type 2 diabetes mellitus.